Phenological phase affects carrot seed production sensitivity to climate change – A panel data analysis - Asharp, G.; McGill, S.; Ward, A.; Sofkova-Bobcheva, S.; Pieralli, S. (Elsevier, 2023)
New Zealand is a major producer of carrot seeds globally. Carrots are an important nutritional crop for human consumption. Since the growth and development of carrot seed crops mainly depend on climatic factors, seed yield is extremely susceptible to climate change. This modeling study was undertaken using a panel data approach to determine the impact of the atmospheric conditions (proxied by maximum and minimum temperature) and precipitation during the critical growth stages for seed production in carrot, viz., juvenile phase, vernalization phase, floral development phase, and flowering and seed development phase on carrot seed yield. The panel dataset was created using cross-sections from 28 locations within the Canterbury and Hawke's Bay regions of New Zealand that cultivate carrot seed crops and time series from 2005 to 2022. Pre-diagnostic tests were performed to test the model assumptions, and a fixed effect model was selected subsequently. There was significant (p < 0.01) variability in temperature and rainfall throughout different growing phases, except for precipitation at the vernalization phase. The highest rate of changes in maximum temperature, minimum temperature, and precipitation were recorded during the vernalization phase (+0.254 °C per year), floral development phase (+0.18 °C per year), and juvenile phase (−6.508 mm per year), respectively. Based on marginal effect analysis, the highest significant influence of minimum (187.724 kg/ha of seed yield decrease for each 1 °C increment) and maximum temperature (1 °C rise increases seed yield by 132.728 kg/ha), and precipitation (1 mm increment of rainfall decreases the seed yield by 1.745 kg/ha) on carrot seed yield were reported at vernalization, and flowering and seed development, respectively. The minimum and maximum temperatures have a higher marginal effect on carrot seed production. Analysis of the panel data demonstrates that the production of carrot seeds will be vulnerable to climatic change.
Keywords: Carrot seed crop; Marginal effect; New Zealand; Phenology; Regression; Seed yield